et f   R--> R be defined by f(x) = 3x -4, then find f^-1(x

Asked by kalyani | 29th Jul, 2018, 07:20: AM

Expert Answer:

f(x) = y = 3x - 4
y + 4 = 3x
x = begin mathsize 16px style fraction numerator straight y plus 4 over denominator 3 end fraction end style
begin mathsize 16px style straight f to the power of negative 1 end exponent left parenthesis straight x right parenthesis space equals space fraction numerator straight x plus 4 over denominator 3 end fraction end style

Answered by Sneha shidid | 30th Jul, 2018, 10:30: AM